If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17(b + -4) = 0 Reorder the terms: 17(-4 + b) = 0 (-4 * 17 + b * 17) = 0 (-68 + 17b) = 0 Solving -68 + 17b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '68' to each side of the equation. -68 + 68 + 17b = 0 + 68 Combine like terms: -68 + 68 = 0 0 + 17b = 0 + 68 17b = 0 + 68 Combine like terms: 0 + 68 = 68 17b = 68 Divide each side by '17'. b = 4 Simplifying b = 4
| 200=x^3+4x^2+4x | | X-2=11/24 | | 22x-3=20+10x | | F/10-11=9 | | 18=9x-7 | | L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 | | 7x-7*2=49 | | y-5=-5.2(x+4) | | 3(n)=1200 | | 6(-9-5x)=-264 | | 7n-3n=4 | | -12=1/8x | | 1(x)=8(40) | | 130=16t*t+27t | | 20m-19m=16 | | -4r-4.7+2.3r+0.3r+5= | | 7=6(x+4)-6 | | 36x-2=4(5+3x) | | 5x^2-8=-12 | | -12x-165+3x=51 | | 22-×/3=13 | | 130=-16t*t+27t | | 15n+11=6 | | 34-13=3(x-6) |